EGGS AND EARLY LARVAE OF THE SAND WHITING, SILLAGO SIHAMA (FORSSKAL) - Bensam, P (Indian Journal of Fisheries, 2011)
Planktonic eggs of S. sihama have been identified from Mandapam in the south-east coast, based onsimilarities in the ripe ovarian eggs as well as other characters. The ripe ova range in diameter from 0.53to 0.78 mm, have a single oilglobule in the diameter range of 0.150 to 0.167 mm and show faint vacuolationof yolk. The planktonic eggs have diameter range of 0.55 to 0.89 mm, in various stages of development, thesize gradually increasing with progressive development. The oil globules show the same diameter rangeas that of the ripe ova and the yolk has faint vacuolation. In early embryos melanophores appear on theoilglobule and dorsal side of the head. With more development, the above pigmentation increases on thebody also, accompanied by the appearance of diffused xanthophores. Hatching takes place in the afternoonof the day of collection, the newly hatched larva measuring 1.54 mm and its pigmentation is in the form ofmelanophores and diffused xanthophores. The 24-hours old larva measures 2.42 mm, with melanophoresmostly along the dorsal and ventral margins of the body and xanthophores in the form of five vertical bands.By 48-hours (measuring 2.56 mm), the post larval phase has set in, with pigmentation of the eyes, formationof the mouth, etc. The similarities of the present material with those of the eggs and early larvae ofS.japonica as well as the difference from it, are discussed